Derivatives Evaluate the following derivatives. ddx(xe+ex)

Talamancoeb

Talamancoeb

Answered

2022-01-14

Derivatives Evaluate the following derivatives.
ddx(xe+ex)

Answer & Explanation

Debbie Moore

Debbie Moore

Expert

2022-01-15Added 43 answers

Step 1
Given:
ddx(xe+ex)
Step 2
Now,
ddx(xe+ex)
Apply the sum/difference rule: (f±g)=f±g
=ddx(xe)+ddx(ex)
Apply the power rule: d(x)bdx=b(x)b1
Apply the common derivative: ddx(ex)=ex
=exe1+ex
Therefore,
ddx(xe+ex)=exe1+ex

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get your answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?